Understanding the use of technology-enhanced learning spaces in Hong Kong: an exploratory study. Issue 3 (3rd July 2019) - Xu, Yafeng; Chiu, Chuang-Kai; Ye, XinDong
ABSTRACT: The applications of technology-enhanced learning spaces have become a topical subject of research, with many studies conducted on the impact of technology-enhanced learning spaces on students' learning; however, only a small number of these focus on how the spaces affect students' learning. This article will elaborate on how technology-enhanced learning spaces facilitate the learning of students and explain in detail the impact of such spaces on them. Interviews were conducted with 48 postgraduate students who had experienced learning in technology-enhanced learning spaces. The interview data were analysed using the grounded theory approach and a theoretical model was proposed for the process of student learning in technology-enhanced learning spaces. The results demonstrate that three factors: academic motivation, extension of time and space, and externalization and expression, can facilitate student engagement in learning in technology-enhanced learning spaces. In addition, student characteristics is an influential factor in student engagement, while pedagogies also determine the effectiveness of these spaces.